COLLABORATION FOR SAFETY: ANALYSIS OF COLLABORATIVE GOVERNANCE IN TRAFFIC MANAGEMENT - Syaha Rany; Dara Aisyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze Collaborative Governance in improving traffic safety in Medan City. The research method uses a qualitative approach with data collection in the form of in-depth interviews, field observations, and document analysis. The data obtained were analyzed using the variables of the collaboration process (face-to-face dialogue, building trust, commitment in the process, mutual understanding, and interim results) presented by Ansell and Gash (2008). The results of the study show that Collaborative Governance begins with a face-to-face dialogue involving various stakeholders, such as the Medan Police Satlantas, the Medan City Transportation Office, and PT. Jasa Raharja Medan Representative. The dialogue was carried out through formal and informal coordination meetings, as well as discussion forums that discussed traffic safety strategies. Trust between stakeholders is built through transparency in the implementation of duties and routine collaboration, such as safety education activities for the community and the use of technology, such as the Polri Super APP application. Interim results of the collaboration include the implementation of educational programs, such as Police Go to School and Police Go to Campus, which have succeeded in raising traffic safety awareness among students and students. In addition, there are improvements to traffic facilities, such as signs and road infrastructure, to support smooth traffic. The main obstacles in this collaboration include differences in priorities between agencies and lack of community participation. However, collaboration has had a positive impact, especially in increasing public compliance with traffic regulations.